Answer:
Step-by-step explanation:
The triangles are all similar, so corresponding sides are proportional.
__
<h3>x</h3>
long side/short side = x/6 = 12/x
x² = 72 . . . . . . . multiply by 6x
x = 6√2 . . . . . . take the square root
__
<h3>y</h3>
hypotenuse/long side = y/12 = (12+6)/y
y² = 216 . . . . . multiply by 12y
y = 6√6 . . . . . take the square root
Answer:
(4,1,3)
Step-by-step explanation:
Answer:
g(f(x)) = -6x+6.
Step-by-step explanation:
It is given that,
f(x) = -3x + 2 and g(x) = 2x – 5
We need to find g(f(x)).
Put it into g(x).
g(f(x)) = 2(-3x + 2)+2
= -6x+4+2
=-6x+6
Hence, the value of g(f(x)) is -6x+6.
93 x 2 = 186
x = 186 - 112
x = 74
y = 2(80) - 74
y = 160 -74
y = 86
360 - 112 - 74 - 86 = 88
z = (88+86)/2
z = 87